Understand the challenges of using a virtual data room to improve profitable and sustainable business outcomes - Ignatius Septo Pramesworo; B.M.A.S. Anaconda Bangkara; Suwandi Ng; Laros Tuhuteru; Adi Mursalin (Institute of Computer Science (IOCS), 2023)
Understanding the challenges of virtual data and space to increase profitable business is very important in this highly competitive era. For this reason, we have obtained several epidermises that explain the challenges and benefits of a virtual data room so that we can enter the business pot that we obtained electronically from several data sources that were currency ten years ago. We analyze the data under a phenomenological approach which can answer the challenge of this question because the virtual data room is a very innovative and phenomenal matter in supporting business. After collecting data from book and journal sources, we analyze it carefully, involving data coding, data interpretation, and drawing valid and reliable conclusions. After a series of studies and obtaining the discussion results, the challenge of using applications that support business under the virtual data room makes it easy for businesses based on efficiency, safety, flexibility, transparency, and other features. Business people can benefit because they can save and have high productivity following the plan to get a profitable and sustainable business. This Temon will provide a new understanding to support academic activities and other industrial applications.